Mistakes Might Only be Made Once: Canada’s Supply, Inspection, and Conservation of Munitions in the First World War - Pritchard, Kyle (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2023)
Canada was a significant producer of munitions for the Western Front during the First World War. It supplied roughly a third of the shells produced in the British Empire, contracted hundreds of businesses, and the industry was the country’s largest employer. As the demand for munitions intensified, experts in finance, industry, and science and technology searched for domestic solutions to the country’s growing munitions supply needs. The resulting investment subsidized war orders in forging and machining and sparked the components necessary to sustain a lasting supply of armaments to the front. In doing so, they also created Canada’s first chemical industries.